CFTA-based current multiplier/divider circuit - Mongkolwai, Pratya; Tangsrirat, Worapong (My University, 2011)
In this paper, the design of a simple analog current-mode multiplier/divider circuit using only two current follower transconductance amplifiers (CFTAs) is presented. With the selection of the applied input currents, the proposed circuit can perform four-quadrant current multiplication, division and current-controlled current amplification, all from the same circuit configuration. The circuit is also insensitive to ambient temperature variations. Additionally, the CFTA non-ideality effects and the non-ideal gain and parasitic component effects on the proposed circuit are studied. The performances of the realized circuit are examined by PSPICE simulations. © 2011 IEEE.
Keywords: Current Follower Transconductance Amplifiers (CFTA); current-mode circuit; divider circuit; multiplier circuit